In this function, we want to go through all of the `x`

values and all of the `y`

values and compute `x*(y - (m*x+b))`

for each of them.

Create a variable called `diff`

that has the sum of all of these values, and return it from the function.

#This is the code I wrote. Can someone explain why it is not correct?

def get_gradient_at_m(x, y, m, b):

diff = 0

N = len(x)

for i in range(N):

y_val = y[i]

x_val = x[i]

diff += (y_val - ((m * x_val) + b))

m_gradient = -2/N * diff

return m_gradient